METHODS FOR ANALYZING LINGUISTIC STYLE MODELS OF WEBSITES - Aliboyeva Nilufar Mahamatali kizi (International Journal of Literature and Language Studies, 2026)
The rapid growth of digital communication has transformed websites into one of the primary channels for information dissemination and interaction. Consequently, the linguistic styles employed on websites have become an important subject of study in linguistics, communication, and information sciences. This article examines the main methods used to analyze linguistic style models of websites, including stylistic analysis, content analysis, statistical methods, corpus linguistics, discourse analysis, and artificial intelligence-based approaches. The study highlights the advantages and applications of these methods in evaluating website effectiveness, audience engagement, and communication strategies.